Use of mechanical insufflation exsufflation and manual techniques in an intubated adult with COVID‐19 positioned in prone—A case study. (18th June 2022) - Apps, Chloe; Morris, Kelly; Allum, Laura; Shah, Neeraj; Mylott, Laura; Hinton, Isobel; Spencer, Danielle; Farley, Rachel; Mitchell, Hannah; Osman, Leyla
Abstract: Background and Purpose: The therapeutic benefits of prone positioning have been described over the last 50 years culminating in a systematic review supporting this management strategy for patients with severe hypoxaemic respiratory failure. Early work detailing treatment approaches for COVID‐19 have advocated the use of prone positioning. Limited data exists regarding physiotherapy intervention in patients with COVID‐19 owing to the recent emergence of this novel disease. Despite the acknowledged beneficial effects of physiotherapy on secretion clearance and lung recruitment in the general critical care population, there is a lack of evidence pertaining to physiotherapeutic intervention for acutely unwell intubated adults in prone lying. Methods: This case study report follows the CARE case report guidelines. One patient with COVID‐19 pneumonitis who underwent physiotherapy intervention in prone lying is discussed. Informed consent was gained from next of kin for data to be published. Results: Treatment techniques including mechanical insufflation‐exsufflation in prone were feasible and well tolerated by this patient with only transient adverse effects noted. Treatment techniques assisted with secretion clearance. Discussion: Further work on safety, feasibility, and efficacy of physiotherapy intervention in patients with and without COVID‐19 in prone will contribute to the evidence base on this subject.